Economic Risk of Wind Farm Investments in UAE: Evaluation through Real Options Approach - Sisodia, Gyanendra Singh; Al Mazrouei, Wafa Mohammed Ebrahim; Mohnot, Rajesh; Rafiuddin, Aqila (International Journal of Energy Economics and Policy, 2023)
This study examines the potential of business investments in wind offshore farm in the United Arab Emirates through projection of five different possible scenarios. The evaluation was done by using real option approach and Monte Carlo simulation imbibing the potential risk on investment with the source of funds used. Our analysis indicates that the return on investments and the risk on delay option remain at the highest degree if the project is financed with 50% government support and 50% investor’s own equity. On the contrary, a 100% bank-financed project yields lowest investments return and lowest risk option to delay. This implies that the financial leverage and the high bank interest rate are significant factors in influencing the economic risk and return of the wind farm project. This research contributes to the existing literature by highlighting the significance of real options application in the most-sought energy sector – wind farm. Moreover, this will pave way for small and medium enterprises (SMEs) in the UAE to invest in this energy field.